DETERMINATION OF PRICE AND CUSTOMER SATISFACTION - Haq, Irfan Nurul (Islamicate Institute, 2017)
Price policy or a value can affect the human mindset, considering its activities by using logic including in considering its needs as a customer of a product. a person or customer will choose which product performance is more effective, efficient and suitable to his needs and according to the value of a price or cost, if the performance is effective, efficient and match with expectations, means customers will feel satisfied and will make the calculation of expenditures for the procurement of products the. Price has a positive and significant impact on customer satisfaction. The main considerations that affect customers are willing to use services include customer satisfaction, service quality, service orientation and pricing in determining the type of service used. The high price is a factor causing customer dissatisfaction so customers are reluctant to use the services provided by the company. The price of a good or service is very influential on customer satisfaction. Consumers use the price as a consideration in determining the purchase of a product, when should the purchase be made and how much the need for products purchased in accordance with the ability of consumer purchasing power. A product must be precise in the determination and determination of the selling price so that it can be accepted by consumers by not neglecting the quality of the product. Under normal circumstances, demand and prices have a negative or reversed relationship. That is, the higher the price is set the smaller the demand.